Pengembangan Sistem Pelaporan Pemeliharaan Stasiun ONLIMO (Online Monitoring) Milik BPPT (Badan Pengkajian dan Penerapan Teknologi) Berbasis Android - Ferlie Deanada Effendi; Herman Tolle; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
For the responsibility of all activities who's been done by station operators, a report to the admin data center is needed. One activities that must be reported is ONLIMO station maintenance activities. However, the current reporting system still using group chat rooms, which makes the admin difficult to get all the data. In addition, there were also difficulties in recording sensor sparepart replacement. So, a system is needed to simplify reporting process at Badan Pengkajian and Penerapan Teknologi (BPPT). The system is implemented on mobile application because a lot of station operators using Android device and on server side using the website platform. For development, agile method is used because it suitable with the process of evaluating research at BPPT. The functional test results found that all feature was valid. While for non-functional testing, we found usability value is 75 which shows that the system is good but needed repairs, the system needs internet connection for reliability aspects, and the system can selecting users well for security aspects. For the effectiveness level obtained 100% where all users can use the system effectively, and for system efficiency is 0.0103 goals/sec which indicates the ONLIMO reporting system already effective and efficient.